PENGARUH DIKLAT, DISIPLIN KERJA, DAN LOYALITAS KERJA TERHADAP KINERJA PEGAWAI PADA BAGIAN SEKRETARIAT DAERAH PEMERINTAH KOTA (PEMKO) BATAM - Nurmayunita; Rini Elfina; Dewi Permatasari (LPPM Universitas Ibnu Sina, 2021)
The regression coefficient is significant or the DIKLAT variable has an effect on Employee Performance at the Regional Secretariat of the Batam City Government. The regression coefficient is significant or the Work Discipline variable affects the Employee Performance variable at the Regional Secretariat of the Batam City Government. The regression coefficient is significant or the Job Loyalty variable has an effect on the Employee Performance variable at the Regional Secretariat of the Batam City Government. The Anova test produces an F count of 12.030> F table of 2.64 with a significance level (probability number) of 0.05. F count> F table then Ho is rejected and H1 is accepted. Then the regression coefficient X1 (DIKLAT), X2 (Work Discipline) and X3 (Work Loyalty) together have a significant effect on variable Y (Employee Performance) at the Regional Secretariat of the Batam City Government.